The implementation of cooperative learning as a learning management strategy to improve students' learning outcomes at SMK Muhammadiyah 04 Medan - Khofifah Laila Ramadhani Harahap; Darmawati Darmawati (Lembaga Riset Mutiara Akbar, 2026)
This study aimed to analyze the effectiveness of implementing Cooperative Learning as a learning management strategy to improve students' learning outcomes at SMK Muhammadiyah 04 Medan. The study employed a quantitative approach using an experimental research design involving an experimental group and a control group. The sample consisted of 56 eleventh-grade students, equally divided into two classes. Data were collected through pre-tests and post-tests and analyzed using SPSS version 22, including descriptive statistics, normality tests, homogeneity tests, paired-samples t-tests, and independent-samples t-tests. The findings revealed that the mean post-test score of the experimental class was 84.82, while the control class achieved a mean score of 78.25. The independent-samples t-test produced a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between students taught using the Cooperative Learning approach and those taught using the teacher-centered method. These findings demonstrate that Cooperative Learning is an effective learning management strategy for improving students’ learning outcomes. Therefore, Cooperative Learning can be recommended as an alternative instructional management approach to foster a more interactive, collaborative, and student-centered learning environment.